"Human Beings Have a Hard Time Relating to That Which Does Not Resemble Them": Queering Normativity in Nnedi Okorafor's Lagoon. (3rd May 2020) - Ncube, Gibson
Abstract: In this article, I analyse the ways in which Nnedi Okorafor's Afrofuturist novel Lagoon (London: Hodder & Stoughton, 2014) challenges stable and so-called normative identities and ways of being. Lagoon narrates the story of aliens landing in Lagos, Nigeria. Through its presentation of shapeshifting aliens, as well as the use of a plurivocal narrative technique enmeshed with Nigerian folktales and myths, the novel destabilises the notions of stable and fixed identities upon which heteropatriarchy rests. Drawing largely on queer and Afrofuturist theories, I argue that Okorafor's novel imagines alternative futures in which identities and desires are liberated from the rigidity of what is idealised and considered normal. I also argue that Lagoon 's Afrofuturist perspective is unequivocally invested in undoing and working against Western hegemony, especially relating to imagining African realities. I highlight, ultimately, that the reader is integral in the process of creating new African realities.